2019
DOI: 10.7554/elife.48702
|View full text |Cite
|
Sign up to set email alerts
|

Entrained neuronal activity to periodic visual stimuli in the primate striatum compared with the cerebellum

Abstract: Rhythmic events recruit neuronal activity in the basal ganglia and cerebellum, but their roles remain elusive. In monkeys attempting to detect a single omission of isochronous visual stimulus, we found that neurons in the caudate nucleus showed increased activity for each stimulus in sequence, while those in the cerebellar dentate nucleus showed decreased activity. Firing modulation in the majority of caudate neurons and all cerebellar neurons was proportional to the stimulus interval, but a quarter of caudate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 59 publications
5
26
0
Order By: Relevance
“…To detect stimulus omission, the animals had to predict each stimulus timing while maintaining eye fixation until the occurrence of an unexpected stimulus omission. Our previous studies using this behavioral paradigm demonstrated that neurons in the cerebellar dentate nucleus and those in the striatum exhibited periodic firing modulation that was gradually enhanced as the repetition progressed (Ohmae et al, 2013;Kameda et al, 2019). Because different nuclei in the central thalamus receive direct inputs from the deep cerebellar nuclei and the output nodes of the basal ganglia (Alexander et al, 1986;Parent and Hazrati, 1995;Bostan and Strick, 2018), neurons in the central thalamus likely transmit signals from these subcortical structures to the cerebral cortex.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…To detect stimulus omission, the animals had to predict each stimulus timing while maintaining eye fixation until the occurrence of an unexpected stimulus omission. Our previous studies using this behavioral paradigm demonstrated that neurons in the cerebellar dentate nucleus and those in the striatum exhibited periodic firing modulation that was gradually enhanced as the repetition progressed (Ohmae et al, 2013;Kameda et al, 2019). Because different nuclei in the central thalamus receive direct inputs from the deep cerebellar nuclei and the output nodes of the basal ganglia (Alexander et al, 1986;Parent and Hazrati, 1995;Bostan and Strick, 2018), neurons in the central thalamus likely transmit signals from these subcortical structures to the cerebral cortex.…”
Section: Introductionmentioning
confidence: 92%
“…In previous studies in our laboratory, neuronal modulation for each repetitive stimulus was proportional to the ISI in both the deep cerebellar nuclei (Ohmae et al, 2013) and the striatum (Kameda et al, 2019). We next examined the activities of three types of thalamic neurons for different ISIs.…”
Section: Response Properties Of Different Types Of Neuronsmentioning
confidence: 98%
See 1 more Smart Citation
“…First, multiple lines of evidence across species suggest a central role for the central thalamus in timing movements (Tanaka, 2006;Lusk et al, 2020;Wang et al, 2020). Second, the authors can leverage their own prior investigations of signals in cerebellar nuclei and striatum (Ohmae et al, 2013;Kameda et al, 2019) to determine which components of thalamic activity might rely on these dominant inputs to the central thalamus.…”
mentioning
confidence: 99%
“…The prediction error activities elevated from IC to MGB to AC and from lemniscal to non-lemniscal regions. Other subcortical regions such as the cerebellum ( 91 ) and basal ganglia ( 92 ) were also known to be associated with the sensory prediction processing. However, DD has mainly been linked with the higher-order processing in predictive coding based on the temporal profile of the MMN, where the lower order response activates earlier (~100 ms) at the AC while the higher-order DD signal becomes visible in a later time window at the frontal area [100–200 ms after the stimulus onset; ( 93 95 )].…”
Section: Neural Basis Of Mismatch Negativity Under the Predictive Codmentioning
confidence: 99%